Breaking the Silence: Articulating the Memories of the Tanjung Priok Victims - Wahyudi Akmaliah (Journal of Indonesian Social Sciences and Humanities, 2015)
For the victims of atrocities, the past is not the past: it remains a trauma. The more they try to forget, the more entrenched their memories become. Hence, memory is a means for sustaining their quest for justicea way victims and their advocates can keep faith in their pursuit of truth, accountability and legal restitution. Unlike the situation during the Suharto presidency when the Indonesian people were silenced, this paper is now able to examine the memories, now articulated, of the people a?ected by the Tanjung Priok tragedy, which have appeared since Suhartos fall. This gives momentum to a new phase of political development in which Indonesians, particularly the victims of violence, may break their silence to pursue justice. The following questions need to be asked: what are the circumstances that have encouraged the victims to articulate their memories in the 17 years since Suhartos departure? In what way have they kept their memories fresh? This paper argues that the main reason they articulate their memory is because of the traumas that always haunted them during the Suharto presidency. The trauma and injustices experienced; the torture, gaol, and the stigma attached to them by the Suharto regimes propaganda, all ensured that the general Indonesian social memory of the events at Tanjung Priok was false and distorted. But those sites of memory, the rites, monuments, and memoirs served to strengthen the articulation of those memories to enable some redress after Suharto regime had ended.